Soil shakedown analysis of slab railway tracks: Numerical approach and parametric study. (September 2018) - Alves Costa, P.; Lopes, P.; Silva Cardoso, A.
Abstract: A procedure for analyzing the shakedown limit load of non-ballasted railway tracks is presented. The shakedown theory is formulated based in the Melan's shakedown lower bound theorem for frictional soils, i.e., adopting the Mohr-Coulomb yielding criteria. The shakedown analysis is enlarged regarding to solutions presented by other authors by incorporating the at rest stress state in the ground. The 3D cyclic stresses induced by the train passage are computed using an efficient numerical model based on the 2.5D approach. The designed model is then used to perform a comprehensive parametric study where it is concluded that the increase of the train speed up to the critical speed of the track-ground system is responsible for a significant decrease of the shakedown limit load. Moreover, it is shown that neglecting the at rest stress state in the ground gives rise to a strong underestimation of the shakedown limit load and that train geometry plays a relevant role in the estimation of the shakedown limit load. From the range of parametric studies conducted it is shown that slab track systems are robust solution and there is space for a rational optimization namely in what concerns to the thickness and stiffness of the hydraulic bounded layers ("poor concrete layer") that are generally placed beneath the track concrete slab.